KINERJA BETON SELF COMPACTING CONCRETE DENGAN BAHAN TAMBAH LIMBAH PET - Raka Kana Pila; Amalia; Jonathan Saputra (Politeknik Negeri Jakarta, 2022)
Self Compacting Concrete (SCC) is only has high flow and pass abilities at the formwork and reinforcementsystems, but also no required vibration work for compaction. This research aims to investigate the physicaland mechanical behavior of fresh and hard concrete. This research was arranged by making SCC concretespecimens with an initial 0.3 according to ACI 211.4R- 93, and statistical methods of regression with SPSS.Objects were tested using a polyethylene terephthalae (PET) variation of 0%, 0.30%, 0.50%, 1.00% and0.8% superplastisizer. The physical behavior of the concrete SCC which were tested consists of flowability,passing ability, binding time and weight. For the mechanical behavior of concrete SCC which were testedconsists of compressive strength, split tensile strength, tensile strength, and elastic modulus. The results ofthis research indicate that the use of PET in SCC can increase the passing ability by 0.92, PET can increasethe weight value of SCC up to 1.16%. SCC binding time with 0.50% PET has the fastest binding time of232 minutes. The compressive strength of concrete using 1.00% PET at the age of 3, 7, 14, and 28 dayshad the greatest value. The split tensile strength of 1.00% PET has the largest value, spesifically 2.48 Mpa.In the flexural tensile strength test, the use of 0.50% PET and 1.00% PET increased the flexural strengthby 6.45% -17.37% compared to the flexural strength at 0% PET. The modulus of elasticity increased in allvariations of PET by 8.34% -25.08% compared to SCC without PET. Based on testing the quality of freshconcrete and hard concrete, the optimum variation in the use of PET is 1.00%Keywords: Compressive strength; PET; SCC